Prevention of STD/ Aids: an approach close to adolescents families - Figueiredo, Marcos Antonio de Castro; Rissi, Maria Rosa Rodrigues (Brazilian Journal of Sexually Transmitted Diseases, 2022)
A sample consisting of 40 family members who care for their patients with Aids at home was assessed on the basis of affective/cognitive attitude scales in order to detenrune the beliefs and social representations related to the disease, the patient and the treatment he receives. The scales, which consist of 17 items, permitted the evaluation of attitude components in six dimensions previously isolated on the basis of Factorial Analysis: a) psychological effects of contamination with HIV, b) fonns of contagion. C) treatment, d) delegation/withdrawal, e) agony / distention, f) fear of contagion. The results permitted us to identify among the relatives of the patients well established cognitions about the exile imposed on persons with Aids, the irreversible and desegregating effect of HIV infection of family coexistence, the importance of maintaining a link with life, the hope, and the need for psychological support so that home care may be provided. Considering the conception of programs aiming at guidance and support for the relatives of the patients, tbese results indicate the relevance of psychological follow-up for these persons and of an attempt to reconstruct the family structures affected by the presence of the patient at home.